The remains of the day - Ishiguro, Kazuo (Everyman's Library, 2012)
"In the summer of 1956, Stevens, the ageing butler of Darlington Hall, embarks on a leisurely holiday that will take him deep into the English countryside and into his past . . . A haunting tale of lost causes and lost love, The Remains of the Day, winner of the Booker Prize, contains Ishiguro's now celebrated evocation of life between the wars in a Great English House - within its walls can be heard ever more distinct echoes of the violent upheavals spreading across Europe."